Lawyers, swamps, and money U.S. wetland law, policy, and politics - Gardner, Royal C. (Island Press, 2011)
Lawyers, Swamps, and Money is an accessible, engaging guide to the complex set of laws governing America's wetlands. After explaining the importance of these critical natural areas, the book examines the evolution of federal law, principally the Clean Water Act, designed to protect them. Readers will first learn the basics of administrative law: how agencies receive and exercise their authority, how they actually make laws, and how stakeholders can influence their behavior through the Executive Branch, Congress, the courts, and the media. These core concepts provide a base of knowledge for successive discussions of: the geographic scope and activities covered by the Clean Water Act the curious relationship between the U.S. Army Corps of Engineers and the Environmental Protection Agency the goal of no net loss of wetlands the role of entrepreneurial wetland mitigation banking the tension between wetland mitigation bankers and in-lieu fee mitigation programs wetland regulation and private property rights. The book concludes with insightful policy recommendations to make wetlands law less ambiguous and more effective. A prominent legal scholar and wetlands expert, professor Royal C. Gardner has a rare knack for describing landmark cases and key statutes with uncommon clarity and even humor. Students of environmental law and policy and natural resource professionals will gain the thorough understanding of administrative law needed to navigate wetlands policy-and they may even enjoy it.